The Role of Hydrogen Peroxide in Mediating the Mechanical Wounding-Induced Freezing Tolerance in Wheat - Si, Tong; Wang, Xiao; Zhao, Chunzhao; Huang, Mei; Cai, Jian; Zhou, Qin; Dai, Tingbo; Jiang, Dong (Frontiers in Plant Science, 2018)
Systemic wound response (SWR), a well-characterized systemic signaling response, plays crucial roles in plant defense responses. Progress in understanding of the SWR in abiotic stress has also been aided by the researchers. However, the function of SWR in freezing stress remains elusive. In this study, we showed that local mild mechanical wounding enhanced freezing tolerance in newly occurred systemic leaves of wheat plants (Triticum aestivum L.). Wounding significantly increased the maximal photochemical efﬁciency of photosystem II, net photosynthetic rate, and the activities of the antioxidant enzymes under freezing stress. Wounding also alleviated freezing-induced chlorophyll decomposition, electrolyte leakage, water lose, and membrane peroxidation. In addition, wounding-induced freezing stress mitigation was closely associated with the ratio between reduced and oxidized glutathione (GSH/GSSG), and the ratio between ascorbate and dehydroascorbate (AsA/DHA), as well as the contents of total soluble sugars and free amino acids. Importantly, pharmacological study showed that wounding-induced freezing tolerance was substantially arrested by pretreatment of wheat leaves with the scavenger of hydrogen peroxide (H2O2) or the inhibitor of NADPH oxidase (RBOH). These results support the hypothesis that local mechanical wounding-induced SWR in newly occurred leaves is largely attributed to RBOH-dependent H2O2 production, which may subsequently induce freezing tolerance in wheat plants. This mechanism may have a potential application to reduce the yield losses of wheat under late spring freezing conditions.